BIJAK MEMILIH KONTRASEPSI EFEKTIF PADA MASA PANDEMI COVID-19 - Bardiati Ulfah; Pratiwi Puji Lestari; Fika Aulia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2021)
Background one of the government's efforts to achieve this target is by taking several steps, namely increasing the use of family planning that is more effective and efficient in the long term. Long-term contraceptives are very helpful for acceptors during the Covid19 pandemic where they do not have to frequently contact the officers. The use of long-term family planning such as implants and IUDs has 99% effectiveness with a failure rate of only 0.05% for 100 women. Program Objectives: to increase mother's knowledge about the choice of long-term effective contraception in the Middle Alalak class of pregnant women, Banjarmasin City. Method of Implementation: This activity uses the seminar method and questions and answers about the selection of long-term effective contraception Results and Conclusions: After carrying out this community service activity, the conclusion that can be drawn is that there is an increase in knowledge of pregnant women about choosing long-term effective contraception. The hope is that pregnant women after giving birth will be able to understand and determine which effective contraception to choose.